Correction to: A randomised controlled demonstration trial of multifaceted nutritional intervention and or probiotics: the healthy mums and babies (HUMBA) trial - Karaponi Okesene-Gafa; Minglan Li; Rennae S. Taylor; John M. D. Thompson; Caroline A. Crowther; Christopher J. D. McKinlay; Lesley M. E. McCowan (BMC, 2018)
In our 'Primary Outcomes' we made a typographical error [1]; the mean weekly weight gain should read >0.27 kg instead of >0.22 kg. The 'Primary Outcomes' should read as follows